2022
DOI: 10.21608/aimj.2022.125081.1862
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Adding Vitamin D Supplement to Clomiphene Citrate For Induction Of Ovulation In Cases Of Overweight PCOS Women

Abstract: Background: Polycystic ovary syndrome had unclear etiology, affecting 6-12% of females due to undetermined optimal treatment. Studies indulge vitamin D in pathogenesis of PCOS but without evidence demonstrating its effect on PCOS. Aim of the work: Our objective is evaluation of vitamin D supplementation on ovulation in sub-fertile females with PCOS. Patients and methods: Two hundred cases of PCOS at Al-Azhar University Hospital and Damanhour teaching Hospital were selected based on clinical diagnosis, ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…However, Rashidi H et al 39 found no such correlation between vitamin D, high cholesterol levels and IR. The emerging evidence is supporting vitamin D supplementation in improving anovulation and use of vitamin D supplementation with clomiphene is bene cial in improving pregnancy rates 40 . Recently, a systematic review of RCTs evaluated vitamin D use with placebo or with Metformin and reported bene cial effect of vitamin D on follicular development versus no use and improved menstrual regularity in patients with combined use of vitamin D and Metformin 41 .…”
mentioning
confidence: 99%
“…However, Rashidi H et al 39 found no such correlation between vitamin D, high cholesterol levels and IR. The emerging evidence is supporting vitamin D supplementation in improving anovulation and use of vitamin D supplementation with clomiphene is bene cial in improving pregnancy rates 40 . Recently, a systematic review of RCTs evaluated vitamin D use with placebo or with Metformin and reported bene cial effect of vitamin D on follicular development versus no use and improved menstrual regularity in patients with combined use of vitamin D and Metformin 41 .…”
mentioning
confidence: 99%